The Palgrave Handbook of Sexuality Education (Springer Nature, 2021)
This authoritative, state-of-the-art Handbook provides an authoritative overview of issues within sexuality education, coupled with ground-breaking discussion of emerging and unconventional insights in the field. With 32 contributions from 12 countries it definitively traces the landscape of issues, theories and practices in sexuality education globally. These rich and multidisciplinary essays are written by renowned critical sexualities studies experts and rising stars in this area and grouped under four main areas: